Nanomechanical responses of human hair. (March 2016) - Samanta, Aniruddha; Bhattacharya, Manjima; Dalui, Srikanta; Acharya, Megha; Das, Pradip Sekhar; Chanda, Dipak Kr.; Acharya, Saikat Deb; Sivaraman, Sankar Kalidas; Nath, Shekhar; Mandal, Ashok Kumar; Ghosh, Jiten; Mukhopadhyay, Anoop Kumar
Abstract: Here we report the first ever studies on nanomechanical properties e.g., nanohardness and Young׳s modulus for human hair of Indian origin . Three types of hair samples e.g., virgin hair samples (VH), bleached hair samples (BH) and Fe-tannin complex colour treated hair samples (FT) with the treatment by a proprietary hair care product are used in the present work. The proprietary hair care product involves a Fe-salt based formulation. The hair samples are characterized by optical microscopy, atomic force microscopy, field emission scanning electron microscopy, energy dispersive X-ray spectroscopy (EDAX) genesis line map, EDAX spot mapping, nanoindentation, tensile fracture, and X-ray diffraction techniques. The nanoindentation studies are conducted on the cross-sections of the VH, BH and FT hair samples. The results prove that the nanomechanical properties e.g., nanohardness and Young׳s modulus are sensitive to measurement location e.g., cortex or medulla and presence or absence of the chemical treatment. Additional results obtained from the tensile fracture experiments establish that the trends reflected from the evaluations of the nanomechanical properties are general enough to hold good. Based on these observations a schematic model is developed. The model explains the present results in a qualitative yet satisfactory manner. Graphical abstract: Highlights: Correlation of nano and macromechanical properties with microstructural aspects. Nanomechanical properties are sensitive to measurement locations. The macromechanical properties treated (FT) hairs are highest.